Evidence for the Inhibitory Control-Based Languagenon- Specific Lexical Selection in Bilinguals - Gopee Krishnan; Shivani Tiwari (Journal of All India Institute of Speech and Hearing, 1970)
In the context of the ongoing and overwhelming debate on the 'language-specific' versus 'language non-specific' nature of bilingual lexical selection, the current study aimed at investigating this issue using a 'semantic relatedness judgment' paradigm. A group of proficient Malayalam-English bilinguals were required to judge the semantic relatedness (i.e., semantically related vs. unrelated) of word pairs in two language conditions (viz. monolingual – L2-L2 & cross-lingual – L2-L1).The semantically related monolingual and cross-lingual stimuli were judged faster compared to their semantically unrelated counterparts. Monolingual word pairs were judged faster compared to their cross-lingual counterparts both in the semantically related and unrelated conditions. Findings of the present study supported the 'language non-specific' nature of lexical selection in bilinguals. In addition to this, it also provided evidence for the role of inhibitory control of the non-target language in bilingual lexical selection.